SUPLEMEN BUKU AJAR TEMATIK MATERI ENERGI ALTERNATIF & SUMBER DAYA ALAM BERBASIS KONTEKSTUAL UNTUK KELAS IV SD - Sandi Haryadi; Ery Tri Djatmika; Punaji Setyosari (Pascasarjana Universitas Negeri Malang, 2017)
The purpose of this research is to develop thematic's supplementary book for the fourth grade with a focus on the study of alternative energy and natural resources material. Thematic's supplementary book was developed based on student characteristics and contextual. The materials were validated in terms of content, language, and design, the materials were tried out to three elementary students in one-to-one evaluation, six elementary students in small-group evaluations, and to twenty nine elementary students in field trial evaluation. The trial results demonstrate the feasibility of teaching materials have a high level. The average validity got 87.90, the practicality 85.76, and the effectiveness 91.95. So it is recomended be implemented as a supporting source in the learning activities, especially in studying alternative energy & natural resources. Tujuan penelitian ini adalah mengembangkan suplemen buku ajar tematik untuk kelas IV SD dengan fokus kajian pada materi energi alternatif & sumber daya alam. Suplemen buku ajar dikembangkan berdasarkan karakteristik siswa dan kontekstual. Suplemen buku ajar divalidasikan pada aspek isi, bahasa, dan desain, selanjutnya diujicobakan kepada tiga siswa pada uji perorangan, enam siswa pada uji kelompok kecil dan 29 siswa pada uji kelompok besar. Hasil uji coba menunjukkan tingkat kelayakan bahan ajar sangat tinggi. Rata-rata kevalidan sebesar 87,90, kepraktisan 85,76, dan keefektifan 91,95. Disarankan bahan ajar ini diimplementasikan untuk sumber pendukung pembelajaran tematik, khususnya materi energi alternatif & sumber daya alam.